EVALUATION OF THE RISK FACTORS FOR CEREBROVASCULARY DISEASES - Berilgen, M. Said; Bulut, Serpil (Fırat University, 2001)
Aim: The aim of this study was to investigate the risk factors for cerebrovascular diseases in patients admitted to our clinic and distribution with respect to stroke type observed in this patients. Material and Method: The present study consisted of totally 90 patients (35 females and 55 males, ranged 35-92 years old ) with cerebrovascular accidents (CVA) who had been admitted or been followed by Neurology Department of Bingöl State Hospital. Of the patients, 78 were ischaemic and 12 were haemorhagic CVA. Results: With the respect to risk factors, there were some risk factors including hypertension 57.3% and 82.3%, smoking 44.4% and 25.7%, diabetes mellitus 28.4% and 21.4%, obesity 28% and 28.6%, coronary artery disease 22.2% and 14.3%, hyperlipidemia 21.8% and 10%, family history of CVA 15.4% and 12.9%, atrial fibrillation 12.2% and 7.1%, alcohol use 9.6% and migraine type headache 0.9% and 4.3% in ischaemic and hemorrhagic CVA, respectively. Although both type CVA have similar risk factors, some of them are significant compared to each other due to pathophysiological differences. Conclusion: In the present study, risk factors and their distribution according to stroke types were examined in patients who had applied to our clinic because of the clinical siyvation of CVA.

Amaç: Bu çalışmada kliniğimize serebrovasküler hastalık tablosu ile başvuran olgularda risk faktörleri ve strok tiplerine göre dağılımının incelenmesi amaçlanmıştır. Gereç ve yöntem: Bu çalışmada Mayıs 1999-Haziran 2001 tarihleri arasında Bingöl Devlet Hastanesi Nöroloji kliniğinde yatarak tedavi görmüş ve nöroloji polikliniğinde geçirilmiş serebrovasküler hastalık (SVH) tanısı ile izlenen yaşlan 35 ile 92 arasında değişen, 35 kadın 55 erkek olmak üzere toplam 90 serebrovasküler hastalık olgusunda risk faktörleri araştırılmıştır. Bulgular: Olguların 78'inin iskemik, 12'sinin hemorajik SVH olduğu görülmüştür. Risk faktörleri incelendiğinde, iskemik ve hemorajik SVH olgularında sırasıyla hipertansiyon %57.3 ve %82.3, sigara içimi %44.4 ve %25.7, diabetes mellitus %28.4 ve %21.4, obezite %28 ve %28.6, koroner arter hastalığı %22.2 ve %14.3, hiperlipidemi %21.8 ve %10, ailede SVH öyküsü %15.4 ve %12.9, atrial fibrilasyon %12.2 ve %7.1, alkol kullanımı %9.6 ve %12.9, migren tipi vasküler başağrısı %0.9 ve %4.3 olarak saptanmıştır. İskemik ve hemorajik SVH için benzer risk faktörleri söz konusu ise de patofizyolojilerindeki farklılığa bağlı olarak bazı faktörlerin iskemik, bazılarının hemorajik SVH için daha ön planda olduğu görülmektedir. Sonuç: Bu çalışmada kliniğimize serebrovasküler hastalık tablosu ile başvuran olgularda risk faktörleri ve strok tiplerine göre dağılımı incelenmiştir.
SEREBROVASKÜLER HASTALIKLARDAKİ RİSK FAKTÖRLERİNİN DEĞERLENDİRİLMESİ